Proceso de liquidación de materiales en la Corporación Nacional Cnel Los Ríos - Tutiven Ríos, Iván Patricio (2017)
The company CNEL is an organization that is dedicated to the distribution, provision and commercialization of electric energy at the national level, started its activities in 2008, with all the regulatory documentation, part of the need of the people since this is a service basic primordial to satisfy their different activities whether they are industrial, commercial or residential, nowadays the service of electrical energy is indispensable for the development of the towns around the world